Update on the Coordinated Efforts of Looking After the Health Care Needs of Children and Young People Fleeing the Conflict Zone of Ukraine Presenting to European Emergency Departments—A Joint Statement of the European Society for Emergency Paediatrics and the European Academy of Paediatrics - Nijman, Ruud G.; Bressan, Silvia; Brandenberger, Julia; Kaur, Davi; Keitel, Kristina; Maconochie, Ian K.; Oostenbrink, Rianne; Parri, Niccolo; Shavit, Itai; Teksam, Ozlem; Velasco, Roberto; van de Voorde, Patrick; et al. (Frontiers in Pediatrics, 2022)
This joint statement by the European Society for Emergency Paediatrics and European Academy of Paediatrics aims to highlight recommendations for dealing with refugee children and young people fleeing the Ukrainian war when presenting to emergency departments (EDs) across Europe. Children and young people might present, sometimes unaccompanied, with either ongoing complex health needs or illnesses, mental health issues, and injuries related to the war itself and the flight from it. Obstacles to providing urgent and emergency care include lack of clinical guidelines, language barriers, and lack of insight in previous medical history. Children with complex health needs are at high risk for complications and their continued access to specialist healthcare should be prioritized in resettlements programs. Ukraine has one of the lowest vaccination coverages in the Europe, and outbreaks of cholera, measles, diphtheria, poliomyelitis, and COVID-19 should be anticipated. In Ukraine, rates of multidrug resistant tuberculosis are high, making screening for this important. Urgent and emergency care facilities should also prepare for dealing with children with war-related injuries and mental health issues. Ukrainian refugee children and young people should be included in local educational systems and social activities at the earliest opportunity.